2005
DOI: 10.1080/02640410400023258
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of dietary supplements and positive drug tests in sport

Abstract: The use of dietary supplements is widespread in sport and most athletes competing at the highest level of competition use some form of dietary supplementation. Many of these supplements confer no performance or health benefit, and some may actually be detrimental to both performance and health when taken in high doses for prolonged periods. Some supplements contain excessive doses of potentially toxic ingredients, while others do not contain significant amounts of the ingredients listed on the label. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
2
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(149 citation statements)
references
References 16 publications
3
128
2
16
Order By: Relevance
“…Furthermore, of concern is that this study obtained a positive hormonal response in more then 70% of the tested products. This reinforces increasing publicised data about the presence of EDs in healthfood supplements [12,13,27].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, of concern is that this study obtained a positive hormonal response in more then 70% of the tested products. This reinforces increasing publicised data about the presence of EDs in healthfood supplements [12,13,27].…”
Section: Discussionsupporting
confidence: 76%
“…The 'General Food Law Regulation' clearly specifies that medicinal products should not be included in any type of food. However, concerns over the accidental, environmental or deliberate contamination of sport supplements during the manufacturing process or from the raw ingredients have been highlighted in an increasing number of studies reporting the contamination of sport supplements with hormonally active substances [12,13]. Delbeke et al reported the significant presence of pro-hormones and hormones in two sport supplements which did not have hormonal substances listed on the product label [14].…”
Section: Introductionmentioning
confidence: 99%
“…Adulteration is an exemplary repercussion of such laxity. Well documented are instances of diuretics, stimulants, anorectics, or oxidative uncouplers contained in weight loss supplements [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], steroids in performance enhancers [75][76][77][78][79][80], and phosphodiesterase 5 inhibitors contained within male enhancement products [72,74,[81][82][83][84][85][86][87][88][89][90][91][92][93]. At least nine people died in Sweden following exposure to Kratom adulterated with Odesmethyltramadol, a potent opioid analgesic.…”
Section: Supplement Regulationmentioning
confidence: 99%
“…A concern with many supplements on sale, apart from the lack of evidence of efficacy and safety, is the recent spate of reports of contamination of supplements with prohibited substances, including stimulants and anabolic steroids (50) . The amounts present are generally, though not always, too small to be effective in improving performance or to pose a risk to health but can cause a positive drugs test (51) .…”
Section: Dietary Supplementsmentioning
confidence: 99%